Development of Augmented Reality Application for Canang Education Using Marker-Based Tracking Method - Putra, I Kadek Agus Andika; Putra, I Gusti Ngurah Anom Cahyadi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2021)
The aim of this study is to develop an Augmented Reality application with marker-based tracking that use for Canang education. This application was developed with waterfall model. Data collection technique that I use in this study is surveys, interview and literature review. This application can pop up information about types of Canang, when you use that types, and an example picture of the Canang. This application use vuforia software development kit (SDK) for combine the reality object and virtual object use for smartphone with QR Code. The design for information and example picture of Canang is built in Adobe Illustrator and made to Augmented Reality in Unity. Method that use in this study is Marker Based Tracking which identifies marker patterns. This application applies multi-target marker-based Augmented Reality so that each type of Canang information is stored and ran on different markers. This application can be medium for education about Canang in general for Hindusm teen.